A novel strong and durable near-surface mounted (NSM) FRP method with cost-effective fillers. (1st January 2021) - Sun, Wei; Lou, Tiejiong; Achintha, Mithila
Abstract: Conventional near-surface mounted (NSM) FRP methods rely on expensive and less durable epoxy-filler bond to transfer tensile force from FRP reinforcements into concrete elements, generally failing to fully develop the tensile strength of FRP reinforcements. In this paper, cost-effective and potentially more durable fillers (e.g. cement-based paste and ceramic tile adhesive) combined with anchorages have been proposed to improve conventional NSM FRP methods. Experimental results demonstrate that the proposed NSM methods are able to make full use of FRP reinforcements, suggesting excellent compatibility between fillers and the proposed method. Further mechanical improvements can be achieved by evenly distributing the FRP material of one groove into multiple grooves. Moreover, the study tends to use high-viscosity cement filler for facilitating FRP installation especially on the bottom or side of concrete elements. The application of flexural reinforcement on the side of concrete elements have also been explored, aiming to deliver a much easier FRP installation. It is believed that the paper presents feasible improvements for NSM methods. Test results suggest that those improvements can achieve a stronger and potentially more durable NSM method with cost-effective fillers.